POLITIK HUKUM DALAM UNDANG-UNDANG NOMOR 5 TAHUN 1998 TENTANG KONVENSI MENENTANG PENYIKSAAN DAN ERLAKUAN ATAU PENGHUKUMAN LAIN YANG KEJAM, TIDAK MANUSIAWI, ATAU MERENDAHKAN MARTABAT MANUSIA - Kaharuddin Syah (Maleo Law Journal, 2019)
The threat to the existence of human rights can come from two axes, namely threats from abroad and from within the country. In the records and records of the mass and electronic media, it is evident that what sustained efforts are carried out by a number of human beings to destroy or oppose the existence of human rights itself. In this regard, the ratification of the anti-torture convention carries total political consequences in the field of human rights. This is very interesting to study, especially from the standpoint of Indonesian legal politics, which so far has been judged by legal political observers to always reflect the character of orthodox / authoritarian law during the thirty-two-year new order government  Keyword: Political Law